Late‐onset noninfectious interstitial lung disease following autologous haematopoietic stem cell transplantation in paediatric patients. Issue 6 (12th April 2016) - Lee, Yoon‐Kyoung; Huh, Rimm; Kim, Jihyun; Ahn, Kangmo; Sung, Ki Woong; Cho, Joongbum
Abstract: Background and objective: High‐dose chemotherapy (HDCT) followed by autologous haematopoietic stem cell transplantation (HSCT) is widely used in paediatric cancer patients, but few data about noninfectious interstitial lung disease (ILD) following this treatment are available. Therefore, we aimed to evaluate the incidence, clinical features and risk factors of noninfectious ILD after HDCT in paediatric patients. Methods: This was a retrospective cohort study of paediatric solid tumour patients who underwent HDCT and autologous HSCT between 1997 and 2012. ILD was diagnosed using clinical symptoms and radiography after excluding cardiac, renal and infectious causes. Risk factors were analysed using a Cox proportional hazard regression model. Results: Three hundred and forty patients were enrolled, and the median age was 3 years (interquartile range 1–7). Eight patients (2.4%) were diagnosed with noninfectious ILD. The median duration of symptom onset was 30 months (range 7–74). Six (75%) of eight ILD patients died during the study period, even though steroids were administered for treatment. High‐dose cyclophosphamide use (hazard ratio = 11.37, 95% confidence interval = 1.38–93.32, P  = 0.023) and sex (hazard ratio = 0.10, 95% confidence interval = 0.01–0.84, P  = 0.034) were associated with late‐onset, noninfectious ILD upon multivariate analysis. Conclusion: The incidence of noninfectious ILD after HDCT and autologous HSCT was not negligible, and the clinical features of ILD showed late onset and a poor prognosis. Female gender and high‐dose cyclophosphamide treatment may be risk factors for noninfectious ILD, but further studies with a larger number of ILD patients are suggested. Abstract : We investigated noninfectious interstitial lung disease after autologous transplantation in 340 paediatric patients. The incidence was 2.4%. The symptom onset was late and the prognosis was poor. High‐dose cyclophosphamide and female gender were risk factors of interstitial lung disease.